Eco-friendly interpenetrating network hydrogels integrated with natural soil colloid as a green and sustainable modifier for slow release of agrochemicals. (1st October 2020) - Zhang, Quan; Yu, Gaobo; Zhou, Qichang; Li, Jiacheng; Feng, Yuhong; Wang, Longzheng; Tang, Yiyuan; Peng, Yang
Abstract: Natural soil colloid, an important component of natural soil, has high specific surface area and strong adsorbability. Although natural soil colloids are ubiquitous in natural subsurface environments, they have not been utilized to synthesize composite materials for any practical application. In this work, a series of eco-friendly interpenetrating polymer network hydrogels integrated with natural soil colloid were synthesized via the ionic crosslinking of alginate and covalent cross-linking of polyacrylamide (PAM) in the aqueous dispersion of natural soil colloid. The natural soil colloid was extracted from the natural soil by a simple, green and sustainable process, without any formation of pollution. The swelling characteristic experiment showed that the soil colloid in polymeric matrix accelerated water absorption by the hydrogels. Hydrogels released 34.4% of pesticide and 56.9% of fertilizer loaded during 54 and 30.5 h at the slowest release rates, respectively. The release data indicated that the hydrogels could release the fertilizer and the pesticide in a slow manner. These findings show that natural soil colloid can be used as a green and sustainable modifier to improve the slow release of hydrogels. Therefore, the synthesized hydrogels integrated with natural soil colloid show great potential as carriers of agrochemicals in modern agriculture and horticulture. Graphical abstract: Image 1 Highlights: The natural soil colloid was utilized to synthesize composite materials. The natural soil colloid was extracted by a simple, green and sustainable process. The soil colloid in the polymeric matrix accelerates water absorption via the hydrogels. The soil colloid in the polymeric matrix enables the pesticide and fertilizer to be sustainably released by the hydrogels.